Penerapan Algoritma Finite State Machine pada Game Horror 3D untuk Melestarikan Budaya Tradisional Bangsa Berbasis Android - Septa Septa; Aries Saifudin (Teknik Informatika Universitas Pamulang, 2019)
Indonesia is a country that is rich in its unique culture, but modern society is embarrassed to admit it, especially mythical culture such as the characters of native Indonesian ghosts, heirlooms, historic places that are mystical and many more. Though the myth culture is a lot of positive values that can be used as lessons. To introduce the culture of myth, it can take advantage of technological advances, one of which is games. By building an Android-based 3-dimensional horror game that adds experience about Indonesian culture. To help the animation control system with the 3-dimensional game model requires a method, one of which uses finite state machine (FSM). The advantages of this FSM are very simple, efficient, easy to develop and reliable in overcoming a wide variety of situations. From the results of the implementation and testing, it can be concluded that the game built can add to the experience of Indonesian culture based on the percentage of respondents of 77.8%, and the implementation of the finite state machine method works well and according to the wishes. This can be observed when playing enemy animation games running according to certain conditions and have been running according to the design that has been made.